Durability properties of steel, polyamide, and polyethylene fiber-reinforced geopolymer mortar made with recycled concrete aggregate and glass powder as fillers - Nazir, Khizar; Canpolat, Orhan; Uysal, Mucteba (ELSEVIER, 2023)
This research produced steel, polyamide, and polyethylene fiber-reinforced metakaolin-red mudbased geopolymer mortar with recycled concrete aggregate (RCA) and waste glass powder (GP) as fillers. To study the durability behavior, a series of experiments were conducted to investigate the resistance of manufactured geopolymer mortar against high temperatures (300 & DEG;C, 600 & DEG;C, and 900 & DEG;C), freeze-thaw (180 cycles), and sulfate attacks (10% sodium sulfate and 10% magnesium sulfate solution). According to the findings, using GP as a filler material by replacing RCA 50% produced the best strength results. Moreover, adding fibers to the mixture showed significant improvement in durability properties. Steel fiber-reinforced mixtures showed better resistance against high temperatures and freeze-thaw cycles than the rest of the series. Steel fibers improved the flexural strength to 15.58% at 300 & DEG;C, 19.26% at 600 & DEG;C, and 42.94% at 900 & DEG;C compared to the control mixture. Against sulfate attack, fiber-reinforced mixtures behaved better than nonfibrous control mixtures. Weight loss was observed after high-temperature exposure, while the increased weight of samples was observed after exposure to freeze-thaw cycles and sulfate attack. SEM analysis observed a weak interfacial transition zone between the matrix and the fibers.
Keywords: Geopolymer; Recycled aggregate; Glass powder; Fibers; Mortar; F FLY-ASH; MECHANICAL-PROPERTIES; PORTLAND-CEMENT; ELEVATED-TEMPERATURE; COMPRESSIVE STRENGTH; WASTE GLASS; METAKAOLIN; RESISTANCE; BEHAVIOR; PERFORMANCE; Construction & Building Technology; Engineering